A Dance With Dragons : A Song of Ice and Fire #5 - Martin, George R. R. (New York : Bantam Books, 2011)
New threats emerge to endanger the future of the Seven Kingdoms, as Daenerys Targaryen, ruling in the East, fights off a multitude of enemies, while Jon Snow, Lord Commander of the Night's Watch, faces his foes both in the Watch and beyond the great Wall of ice and stone.
Keywords: Fantasy fiction